2020
DOI: 10.3389/fnmol.2020.586731
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Transmission of Tau by Autophagic-Endolysosomal Networks and Potential Therapeutic Targets for Tauopathy

Abstract: Tauopathies are a class of neurodegenerative diseases, including Alzheimer's disease (AD), Frontotemporal Dementia (FTD), Progressive Supranuclear Palsy (PSP), Corticobasal Degeneration (CBD), and many others where microtubule-associated protein tau (MAPT or tau) is hyperphosphorylated and aggregated to form insoluble paired helical filaments (PHFs) and ultimately neurofibrillary tangles (NFTs). Autophagicendolysosomal networks (AELN) play important roles in tau clearance. Excessive soluble neurotoxic forms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 133 publications
0
53
0
Order By: Relevance
“…Autophagy can be divided into chaperone-mediated autophagy (CMA), endosomal microautophagy (e-MI), and macroautophagy [162]. Macroautophagy is the major cellular mechanism responsible for removing protein aggregates, such as insoluble tau aggregates [163], long-lived proteins, damaged organelles, and pathogens, whereas CMA [164] and e-MI [165] may degrade soluble neurotoxic forms of tau.…”
Section: Defective Protein Degradationmentioning
confidence: 99%
“…Autophagy can be divided into chaperone-mediated autophagy (CMA), endosomal microautophagy (e-MI), and macroautophagy [162]. Macroautophagy is the major cellular mechanism responsible for removing protein aggregates, such as insoluble tau aggregates [163], long-lived proteins, damaged organelles, and pathogens, whereas CMA [164] and e-MI [165] may degrade soluble neurotoxic forms of tau.…”
Section: Defective Protein Degradationmentioning
confidence: 99%
“…Recent evidence also suggests that LGALS8-mediated autophagy is important in preventing the entry of tau seeds into the cytosol and their subsequent aggregation ( 41 ). Our immunohistochemical studies demonstrate that LGALS8 is localized within neuronal lysosomes where it may play a role in autophagic degradation of intraneuronal tau ( 42 ). Our finding that dual-specificity phosphatase 3 (DUSP3), also known as VH1-related phosphatase (VHR), is localized within postsynaptic processes of both excitatory and inhibitory neurons is also consistent with its proposed role in countering excitotoxicity-induced neuronal death and Aβ accumulation ( 43 ).…”
Section: Discussionmentioning
confidence: 92%
“…While elucidating the precise molecular mechanisms by which Numb controls Tau levels will require further investigation, our findings indicate that Numb-72 promotes the release of native Tau monomers into the extracellular space. Several studies have shown that Tau is not only an intraneuronal protein, but can also be released in the extracellular space via exosomes and ectosomes (72,73,90,91). Although the release of Tau oligomers was reported to contribute to spreading of the pathology, physiological Tau can also be secreted by neurons through exosomes (92)(93)(94), which is thought to serve as a clearance mechanism to prevent pathological Tau formation (73).…”
Section: ! Discussionmentioning
confidence: 99%
“…S5D, F). Finally, we wondered whether Numb might promote the extracellular release of Tau, which is known to help balance intracellular levels in physiological and pathological conditions (72,73). We transfected GFP or Numb-72 in a Tau-expressing stable cell line and measured the levels of total Tau and oligomeric Tau in the culture medium 24 hours later by DotBlot assays.…”
Section: Numb Negatively Regulates Intracellular Tau Levels In An Isoform-specific Mannermentioning
confidence: 99%